From Energy Security to Energy Dominance: US' Blending of Politics and Economics. Issue 2 (3rd March 2020) - Balafas, Vasileios; Fakiolas, Efstathios T.
Abstract: In the aftermath of the successful 'America First' or 'Make America Great Again' presidential election campaign, President Trump's era inaugurated the realm of energy politics. It began with the US withdrawal from the Paris Climate Agreement and the lifting of the US export ban on crude oil. So far, it has been featured in setting aside President Obama's climate change mitigation policy, which emphasized regulation, discouraged oil and gas development, and denounced the extensive exploitation of natural resources. As a whole, the new Trump era favours shale oil and gas drilling, deregulation and the revitalization of the coal industry.This article argues that a switchover of US priorities from energy security to energy dominance is currently in the making. Through the lens of an explanatory framework, the new US political leadership, after a period of economic recession in the wake of the crisis of 2007–2008, has blended economics and politics to improve shale technologies, and take advantage of its rich natural resources, in order to ensure its global superpower role.